Down-to-earth issues in information system use - Ahmad @ Abdul Mutalib, Hawa; Basden, Andrew (Association for Information System (AIS) eLibrary, 2013)
This study proposes a new understanding of IS use that gives attention to the everyday 'Down-To- Earth' (DTE) issues that actually affect the success or quality of IS use. These differ from the kinds of issues discussed in the extant literature on IS use, in at least five main ways. The DTE approach takes the user's everyday perspective rather than that of management, IT suppliers or researchers. It widens the often narrow focus on single aspects of IS use. It recognises the importance of indirect and hidden issues, which are often overlooked. And it provides a way of coping with the plethora of issues that result from this. To achieve this, the DTE approach makes use of the suite of fifteen aspects that emerge from Dooyeweerd's philosophy of everyday life. Empirical research has been undertaken to operationalize the DTE approach as a qualitative analysis method enriched with Dooyeweerd's aspects. This showed that the kinds of issues found by the DTE approach are not only more numerous than with conventional approaches, but also of different kinds, giving a richer and wider picture of IS use. Contributions to theory, methodology and practice are briefly discussed